Assessment of G × E interactions using AMMI, GGE biplot and stability analysis in blackgram (Vigna mungo) - P, SHANTHI; M, GUNASEKARAN; N, MANIVANNAN; D, SASSIKUMAR; M, UMADEVI (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during rainy (kharif) 2020, winter (rabi) 2020–21, summer 2021, rainy (kharif) 2021 and winter (rabi) 2021–22 at National Pulses Research Station, Pudukkottai, Tamil Nadu to assess the stability over environments, G×E interaction through Finlay-Wilkinson, Eberhart and Russell model, AMMI analysis and GGE biplot model for grain yield using 20 blackgram [Vigna mungo (L.)] genotypes in five consecutive seasons with climatic variations. Based on stability analysis the genotypes, viz. VBG17021, VBG17030, VBG18034 and VBN 8 were identified as more stable genotypes across environments with high yielding. In the AMMI model G×E interaction analysis disclosed that a total of 93.7% of interaction was contributed by the first three principal components viz. IPCA1, IPCA2, and IPCA3. The genotypes VBG18048 (G5), VBG17026 (G14), VBG18034 (G18) and VBG18032 (G11) were recorded the IPCA1 values close to zero suggested that these were more stable across environments. The yield of these genotypes were also better than the best check variety VBN8. The genotypes, such as VBG18032 (G17) and VBG18040 (G20) had high positive IPCA1 values showed a positive interaction with the particular environments (E2). Therefore, these genotypes can be recommended for the favourable environment E2 (kharif 2020), whereas the genotypes VBG18043 (G3) and VBG18047 (G4) can be recommended for another favourable environments E3 and E5 (rabi 2020 and 2021). The results of AMMI biplot 1 and 2 and GGE biplot analysis, determined that VBG 18043 (G3) was more stable genotype coupled with high yielding across seasons. The “which- won- where” model of GGE biplot analysis showed that the genotypes VBG18048 (G5) and VBG18034 (G18) were highly suitable for the kharif and rabi seasons and VBG17030 (G16) was suitable for summer season. The analysis of all four models of G×E interaction clearly indicated that the genotype VBG18034 was identified as more stable in all the five environments.